Antidepressant and skeletal muscle relaxant effects of the aqueous extract of the Prosopis cineraria - Mathew George; Lincy Joseph; Abishika Sharma (Universidade de São Paulo, 2012)
The aqueous leaves extract of Prosopis cineraria (AEPC) is used traditionally for the treatment of various CNS disorder. The purpose of this study was to evaluate the extract for antidepressant and skeletal muscle relaxant activity. The antidepressant effect of the extract was evaluated using Forced swim test (FST). The immobility periods of control and treated mice were recorded. The antidepressant-like effect of tested compound was compared to that of imipramine (15 mg/kg. p.o). Muscle relaxant property was studied using rotarod apparatus and total fall off time for standard and control group was recorded. Phytochemical screening revealed the presence of saponins, flavonoids, alkaloids, glycosides, tannins and phenolic compounds. The leaf extract at doses of 200 mg/kg significantly decreased the duration of immobility time in FST. The efficacy of tested extract was found to be comparable to that of imipramine. Our results suggested that the aqueous extract of Prosopis cineraria leaves exerts antidepressant-like effect. O extrato aquoso de folhas de Prosopis cineraria (AEPC) é utilizado, tradicionalmente, para o tratamento de várias disfunções do SNC. O propósito desse estudo foi avaliar o extrato quanto às atividades antidepressiva e relaxante muscular esquelética. O efeito antidepressivo do extrato foi avaliado usando o teste do nado forçado (FST). Registraram-se os períodos de imobilidade dos camundongos controle e dos tratados. O efeito antidepressivo do composto testado foi comparado com a imipramina ((15 mg/kg. p.o). A propriedade relaxante muscular foi estudada usando o cilindro giratório e o tempo total de queda para os grupos padrão e controle foram registrados. A triagem fitoquímica revelou a presença de saponinas, flavonoides, alcaloides, glicosídeos, taninos e compostos fenólicos. O extrato da folha em doses de 200 mg/kg diminui significativamente a duração do tempo de imobilidade no FST. A eficácia do extrato testado foi comparável àquela da imipramina. Nossos resultados sugeriram que o extrato aquoso das folhas da Prosopis cineraria exerce efeito semelhante ao antidepressivo.